Predictors of Hypocalcemia Post Parathyroidectomy for Primary Hyperparathyroidism; a Single Center Study - Khaled A. Obeidat; Nesreen A. Saadeh; Renad Msameh; Ajwad Obeidat; Omar Mar'ey; Ahmad Bakkar; Qutaiba Manasrah (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background Hypocalcemia is a common event after parathyroidectomy for primary hyperparathyroidism (PHPT). This study aimed to explore the incidence of hypocalcemia, determine risk factors, and identify serum biomarkers associated with the development of this condition. Methods A retrospective study that included 116 patients with PHPT who underwent parathyroidectomy at a tertiary care facility in Jordan over 16 years (2006–2022) in this study. Patients were classified as having postoperative hypocalcemia if they developed serum calcium levels < 2.15 mmol/L within the first week following parathyroidectomy. Logistic regression analysis was performed to determine predictors of hypocalcemia. Spearman's rank correlation coefficient and ROC curves were used to assess relationships between variables as well as determine cutoffs for these predictors. Results Of the 116 patients studied, 57.7% developed hypocalcemia after parathyroidectomy. High preoperative alkaline phosphatase (ALP), low preoperative corrected calcium, high preoperative parathyroid (PTH), and younger age were shown to be significantly higher in patients who developed hypocalcemia after parathyroidectomy. Multivariate logistic regression showed a low preoperative corrected calcium level was an independent predictor of postoperative hypocalcemia (p = 0.036). A high level of preoperative alkaline phosphatase was also considered an independent predictor of hypocalcemia development (OR = 1.007, 95% CI: 1.002–1.012). Patients who had pre‐operative ALP less than 208.5 U/L were unlikely to develop postoperative hypocalcemia. Conclusion Our study identified higher preoperative ALP, lower pre‐operative corrected calcium, higher pre‐operative PTH levels, and younger age as risk factors for postoperative hypocalcemia. Preoperative ALP and preoperative corrected calcium were shown to be independent predictors of hypocalcemia development.